Experimental study on failure of temporary earthen slope triggered by intense rainfall. (October 2020) - Song, Xianghua; Tan, Yong
Highlights: Failure models of earthen slopes triggered by rainstorms were investigated by extensive experimental tests. The evolution process of slope failures due to infiltration of rainfall was examined. Failures of slopes associated with different rainfall infiltration scenarios were extensively compared. Abstract: In practice, intense rainfall is one of the major factors contributing to slip failure of man-made or natural earthen slopes, in particular in sandy strata. To explore the failure mechanism of the man-made earthen slope caused by intense rainfall, extensive indoor rainfall experiments in combination of DIC image technology were carried out. The rainfall-triggered slip failure modes were investigated with respect to shot-concrete covering the slope surface (scenario A), the paved roadway on the slope crest (scenario B), and exposed excavation slope (scenario C), respectively. Although the instability evolution mechanisms of these slopes were different for the three rainfall infiltration patterns, the sandy slopes had the same slip failure characteristics of linearity. Generally, the slope faced the highest risk of losing stability in scenario C; scenario A was more dangerous than scenario B at the same rainfall intensity. These results are helpful for professionals to understand the failure development of earthen slope triggered by intense rainfall and then implement appropriate remedial measures to mitigate relevant hazards.